O anjo canibal: sobre alguns temas reunidos entre Walter Benjamin e o Brasil - Santos, Mariana Andrade (2025)
This research proposes to explore the constellation of relations that unite the thought of Walter Benjamin with Brazil. This set of intersections between the German philosopher and our country has been the subject of our investigation from various perspectives throughout our work. In this sense, in our first chapter, we brought to light crossroads between Walter Benjamin and Brazil based on virtual, non-realized confluences and potential encounters, carried out through the historical unfolding of the reception of his thought. In the second chapter, we explored how Benjamin’s thought associates uninterrupted progress and permanent catastrophe with the continuum of human history. We were particularly interested in highlighting the role that the relationship with nature plays in the constitution of this historical intertwining between progress and catastrophe. In the third chapter, we followed a trail, pursuing some clues left by Benjaminian thought, with the aim of investigating the epistemological subject-object relationship. We sought to explore the paths opened by his philosophical reflection by bringing together some questions dispersed in his work, particularly the themes of temporality, language, and the child. Throughout these last two chapters, we propose an investigation into Benjamin’s philosophy with a current and Brazilian perspective: to elaborate an attempt to think about the relevance of his thought in the counter-light of Brazilian indigenous thought. We allow ourselves the adventure of letting the theoretical work with the philosophy of Walter Benjamin be crossed by the reflections of indigenous thinkers, particularly Ailton Krenak and Davi Kopenawa, highlighting how they can dialogue with the themes we propose to explore in Benjaminian thought. Thus, the proposal of this work shares the audacity and the challenge of trying to sow, from these intersections between philosophical tradition and indigenous thought, an opening for new possibilities.